The Quality and Safety of Imported Food: The Danger of Pesticides - Dugar, Batgerel (Mongolian Journal of Chemistry, 2014)
The analysis of pesticide residue in imported food by thin layer chromatography is reported in this work. The pesticide residue was found in 34 samples of 11 kinds fresh harvested vegetables during fall of 2011. DOI: http://dx.doi.org/10.5564/mjc.v12i0.188 Mongolian Journal of Chemistry Vol.12 2011: 131-135